2008
DOI: 10.1007/s10668-007-9138-8
|View full text |Cite
|
Sign up to set email alerts
|

Governance, institutions and the environment-income relationship: a cross-country study

Abstract: This paper examines the environment-income relationship in the context of the Environmental Kuznets Curve (EKC), and explores the possible role that factors like governance, political institutions, socioeconomic conditions, and education play in influencing this relationship. The results suggest that the EKC exists for carbon dioxide emissions for cross-country data over the period 1984-2002. However, there is nothing automatic about this relationship; policies designed to protect the environment may be respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 18 publications
4
53
0
2
Order By: Relevance
“…These outcomes imply that the countries of Asia and Africa have reached the stage where they can start to reduce their CO2 emissions as they grow economically. Hence such results confirm previous efforts that found that a CO2 EKC can occur in countries as they develop economically (Cole et al, 1997;Dietz and Rosa, 1997;Dutt, 2009;Galeotti and Lanza, 1999;Sharma, 2011). Nevertheless, the Latin American region showed insignificant outcomes for both PCI and PCI 2 , thereby implying that an EKC does not exist.…”
Section: Estimation Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…These outcomes imply that the countries of Asia and Africa have reached the stage where they can start to reduce their CO2 emissions as they grow economically. Hence such results confirm previous efforts that found that a CO2 EKC can occur in countries as they develop economically (Cole et al, 1997;Dietz and Rosa, 1997;Dutt, 2009;Galeotti and Lanza, 1999;Sharma, 2011). Nevertheless, the Latin American region showed insignificant outcomes for both PCI and PCI 2 , thereby implying that an EKC does not exist.…”
Section: Estimation Resultssupporting
confidence: 89%
“…The POPG variable turned out insignificant and positive for the Latin American region but significant and negative for the Asian region. The results for the Latin American region verify Dutt (2009); the outcomes for the Asian region, though, seem counter-intuitive since a population increase generally means that greater numbers of people place ever escalating demands on available resources, leading to an accelerated depletion of those resources as well as the creation of larger amounts of waste (Dietz and Rosa, 1997). Nevertheless, an argument can be made that many non-OECD countries have as yet to develop a high enough standard of living to allow their population to truly impact CO2 emissions; these countries have such limited economic development that increased production and consumption from population growth have relatively small impacts on emissions.…”
Section: Estimation Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Most of the studies in this field demonstrate the existence of an Environmental Kuznets Curve (EKC) that links economic growth and the environment (e.g., Baek et al 2009;Castiglione et al 2012;Costantini and Martini 2010;Dutt 2009;Lipford and Yandle 2010;Markandya et al 2006). The theory suggests that economic growth and economic welfare are inter-connected, and environmental protection policy can be seen as a consequence but also as a driver of economic development, since environmental regulation can stimulate innovation that reduces the costs of complying with it (Porter and van der Linde 1995).…”
Section: Environmental Taxation and Economic Growthmentioning
confidence: 99%